Gymnothorax melanosomatus, a new moray eel (Teleostei: Anguilliformes: Muraenidae) from southeastern Taiwan - Loh, Kar-Hoe; Shao, Kwang-Tsao; Chen, Hong-Ming (Zootaxa, 2011)
Gymnothorax melanosomatus new species, is described here on the basis of eight specimens collected from eastern coastal Taiwan at a depth 50–180 m. This new moray eel is distinguished from a closely similar species, G. prolatus, by a combination of the following characters: a uniformly black body when fresh (vs. brown), a relatively long preanal length 58.5 % of TL (vs. 48.9), shorter snout length 17.8 % of HL (vs. 20.0), interobital width 12.2 % of HL (vs. 14.3); more preanal vertebrae 105–109 (vs. 74–86) and total vertebrae 201–211 (vs. 174–190). The male and female are not different in body color and pattern, but the numbers of median intermaxillary teeth are different between the sexes, 0 in male and 2–3 in female.